PENGARUH LIFESTYLE DAN KEMATANGAN EMOSIONAL TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN ONLINE (STUDI KASUS PADA MAHASISWA DI DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG) - Sudaryanto Sudaryanto; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT Mainly Indonesia peape have a tendency to make online clothing purchases. It shows the use and emergency of online purchasing application all around us like OLX, Lazada, Tokopedia, and other. The purpose of this study is know determine the effect of lifestyle and emotional maturity on the decision to buy online clothing in the landungsari Village, Dau district, Malang regency. The sampling technique uing non probality sampling that is a consideration of certain criteria data analysis tool used in this research is multiple Linear regression analysis. The result of this research showed that lifestyle rariables and emotional maturiry have a significant impact of online clothing purchases both simultaneously and partial. Keywords : lifestyle, emotional maturity, online decition clothing